Effects of vest and sled resisted sprint training on sprint performance in young soccer players: a systematic review and meta-analysis - Fernández-Galván, L. M.; Casado, A.; García-Ramos, A.; Haff, G. G. (The Journal of Strength and Conditioning Research, 2022)
The aim of the meta-analysis was to determine the effect of resisted sprint training (RST) on sprint performance in young (<20 years) soccer players and to analyze whether the training equipment (sled or vest) and magnitude of the resistive load (above or below 20% of body mass [BM]) influences the long-term adaptations in sprint performance. Resisted sprint training reduced the acceleration phase time [standardized mean difference (SMD) = -0.41], with greater reduction in sprint time occurring in response to applying resistance with a vest (SMD = -0.70) when compared with a sled (SMD = -0.27). Similar reductions were determined for resistive loads <20% (SMD = -0.55) and =20% of BM (SMD = -0.31). Full sprint time showed a small reduction after RST (SMD = -0.36), regardless of the training equipment (sled: SMD = -0.44; vest: SMD = -0.26) and resistive load (<20% of BM: SMD = -0.40 = 20% of BM: SMD = -0.21). There was a small and nonsignificant reduction in the maximum-velocity phase after RST (SMD = -0.25), which was comparable when the training was performed with vest (SMD = -0.34) or sled (SMD = -0.22). No significant differences in the changes of the acceleration phase time (SMD = 0.05) or full sprint time (SMD = 0.08) were observed between the experimental (sled or vest RST) and control groups (only soccer or unresisted sprint training). In conclusion, RST is effective to improve sprint performance in young soccer players, but the improvements are not superior to unresisted sprint training.